Thermoelectric material composite electrolyte, preparation method thereof and solid-state battery

By introducing thermoelectric materials into polymer electrolytes, the problems of low conductivity and poor interface stability of solid-state batteries are solved, the low-temperature rate performance and cycle stability are improved, and the solid-state batteries with high safety are achieved, which are suitable for wide temperature applications. Simplified production process.

CN119208724APending Publication Date: 2024-12-27CHANGSHA GUNENG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411446888.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The intrinsic conductivity of solid electrolytes in existing solid metal batteries is insufficient, and the electrode-solid electrolyte interface is poor, resulting in poor cycle life. The volume of high-active metal negative electrodes changes greatly during the deposition/stripping process, which easily causes safety problems, especially at low temperatures. The ion conductivity has dropped significantly, which cannot meet the needs of wide temperature applications.

Method used

Inorganic thermoelectric materials, such as Li2SO4, CaS, and CaSe pyrolytic transistors, are introduced into polymer electrolytes. Through the polarization caused by the deviation of the positive and negative charges at low temperatures, the positive and negative dipoles are arranged in a directional manner, significantly improving the conductivity and voltage windows to improve the battery's low temperature magnification performance.

Benefits of technology

It significantly improves the low-temperature rate performance and cycle stability of solid-state batteries, provides a high-safe solid-state battery, and is simple in preparation, low in cost, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208724A_ABST
    Figure CN119208724A_ABST
Patent Text Reader

Abstract

The invention discloses a thermoelectric material composite electrolyte, a preparation method thereof and a solid-state battery, and belongs to the technical field of secondary batteries. The thermoelectric material composite electrolyte comprises a polymer matrix, a lithium salt and thermoelectric material fillers (including Li2SO4 pyroelectric crystals, CaS pyroelectric crystals, CaSe pyroelectric crystals and the like). The thermoelectric material composite electrolyte has relatively high ionic conductivity, voltage stability window and interface stability, can improve the rate capability in a wide temperature range, and shows good low-temperature rate capability and cycling stability when being applied to a solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte, in particular to a thermoelectric material composite electrolyte, and also to a preparation method of the thermoelectric material composite electrolyte and a solid-state battery comprising the thermoelectric material composite electrolyte, belonging to the field of secondary batteries. Background Art

[0002] High-safety and high-energy-density solid-state metal batteries are the key development direction of existing batteries. However, there are still some problems that need to be solved in the large-scale application of current solid-state metal batteries: (1) The intrinsic conductivity of the solid electrolyte is insufficient to meet application requirements; (2) The solid / solid interface stability of the electrode-solid electrolyte is poor, resulting in poor cycle life; (3) The metal negative electrode has a large volume change during the deposition / stripping process and is prone to induce dendrite growth, causing safety problems; (4) The interfacial side reaction problem of highly active metal negative electrodes is serious.

[0003] So far, sulfide, oxide, polymer solid electrolyte and other systems have been developed to improve the safety of batteries and inhibit dendrite growth and interface side reactions. Among them, polymer electrolytes have received widespread attention due to their low cost and simplified process, but they still have the problems of low ion conductivity and poor rate performance. For example, Chinese patents (publication numbers: CN118173863A, CN117712473A, CN114361575A) disclose organic-inorganic composite electrolytes, which use inorganic substances such as oxides or sulfide electrolytes. Although such inorganic fillers have the function of conducting lithium ions, their ion conductivity at low temperatures will still drop significantly, and they cannot meet the requirements of ion conductivity and rate performance for wide temperature range applications. Summary of the invention

[0004] In order to solve the technical problems of low ionic conductivity, narrow voltage window, poor solid / solid interface stability, etc. of existing polymer electrolytes, the first purpose of the present invention is to provide a thermoelectric material composite electrolyte, which effectively improves the ionic conductivity, voltage stability window and interface stability of solid polymer electrolytes by introducing inorganic thermoelectric materials, thereby improving its rate performance over a wide temperature range.

[0005] The second object of the present invention is to provide a method for preparing a thermoelectric material composite electrolyte, which is simple to operate, low in cost, and can be mass-produced.

[0006] The third object of the present invention is to provide a solid-state battery, which uses a thermoelectric material composite electrolyte and has good low-temperature rate performance and cycle stability.

[0007] In order to achieve the above technical objectives, the present invention provides a thermoelectric material composite electrolyte, which includes a polymer matrix, a lithium salt and a thermoelectric material filler; the thermoelectric material filler includes at least one of Li2SO4 pyroelectric crystals, CaS pyroelectric crystals, and CaSe pyroelectric crystals.

[0008] The key to the technical solution of the present invention is to introduce thermoelectric materials into polymer electrolytes. Thermoelectric materials have the characteristics of polarization due to the deviation of the positive and negative charges of their crystals from the center at low temperatures, so that their positive and negative dipoles are oriented. Adding them into polymer electrolytes has the following obvious advantages: on the one hand, thermoelectric materials have good electrical conductivity and can significantly improve the conductivity of composite electrolytes. On the other hand, when the positive and negative charge centers of thermoelectric material crystals deviate and form polarization along the electric field direction, the ionic conductivity and ion migration number and voltage window can be greatly improved, thereby improving the low-temperature rate performance of the battery. As a further preferred thermoelectric material, Li2SO4 pyroelectric crystals are used.

[0009] As a preferred solution, the particle size of the thermoelectric material filler is 1 nm to 1 μm. The smaller the particle size of the thermoelectric filler material, the easier it is to obtain uniformly distributed polarons, so the particle size of the thermoelectric material filler is more preferably 1 nm to 200 nm.

[0010] As a preferred solution, the thermoelectric composite electrolyte includes the following components by weight: 1 part of polymer matrix; 0.05-5 parts of lithium salt; 0.01-5 parts of thermoelectric material. The thermoelectric material should be fully and evenly dispersed in the polymer electrolyte. If the amount is too low, it will be unfavorable to improve the ionic conductivity and voltage window, and if the amount is too high, there will be a risk of short circuit. Therefore, as a further preferred solution, the mass ratio of polymer matrix to thermoelectric material is 1:0.5-3.

[0011] As a preferred solution, the polymer matrix includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride-trifluoroethylene), poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-hexafluoropropylene-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylic acid, polyacrylonitrile, epoxy resin, polyolefin nitrile, polyimide, and polyamide. The preferred polymer matrix is ​​a conventional polymer electrolyte raw material in the prior art. The preferred polymer matrix has a molecular weight greater than 50,000, and the polymer matrix with a larger molecular weight has a better curing and molding effect.

[0012] As a preferred solution, the lithium salt includes at least one of LiPF6, LiTFSI, and LiFSI. The lithium salt is further preferably LiPF6 and / or LiTFSI.

[0013] As a preferred solution, the thermoelectric material composite electrolyte further comprises no more than 5 parts by mass of additives.

[0014] As a preferred solution, the additives include at least one of flame retardant additives such as phosphates, film-forming additives such as borates, film-forming additives such as silane coupling agents, and high-voltage resistant additives such as sulfonates, all of which are conventional electrolyte additives.

[0015] The present invention also provides a method for preparing a thermoelectric material composite electrolyte, comprising the following steps:

[0016] (I) dissolving raw materials including polymer monomers and lithium salt in a solvent to form a solution A;

[0017] (II) adding the thermoelectric material to solution A and stirring evenly to form solution B;

[0018] (III) coating solution B onto a flat plate material and solidifying it into a thin film; or, injecting solution B into a battery and solidifying it into a shape.

[0019] As a preferred embodiment, the solvent includes at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, tetrahydrofuran, N-methylpyrrolidone, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, ethylene glycol dimethyl ether, and ethylene glycol ethyl ether.

[0020] As a preferred solution, the curing conditions are: temperature of 40-120° C., time of 4-24 hours. The curing process is a process of polymerization reaction and solvent volatilization.

[0021] As a preferred solution, the amount of the solvent used is 10 to 90 times the mass of the polymer.

[0022] The present invention also provides a solid-state battery, which includes the thermoelectric material composite electrolyte. In addition to the thermoelectric material composite electrolyte, the other components of the solid-state battery are made of existing conventional materials.

[0023] The present invention provides a method for preparing a thermoelectric material composite electrolyte, comprising the following steps:

[0024] (I) dissolving polymer monomers, lithium salts, initiators and additives in an organic solvent, controlling the mass ratio of organic solvent to polymer to be (10-90):1, stirring and dissolving to form solution A; the organic solvent is one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, tetrahydrofuran, N-methylpyrrolidone, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, ethylene glycol dimethyl ether, and ethylene glycol ethyl ether, preferably, the organic solvent is further preferably one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, and ethylene carbonate; the polymer monomer is a monomer for synthesizing a polymer matrix; when the polymer monomer is an olefin, an initiator AIBN is also introduced, with a content of 0.1% to 5% relative to the mass of the monomer;

[0025] (II) adding a certain proportion of thermoelectric material to solution A and stirring to form solution B;

[0026] (III-1) coating solution B onto a flat material by casting, casting, spin coating or coating, and drying the solvent at a temperature of 40 to 120° C. to form a thin film with a thickness of 15 to 50 μm, which can be directly used as a separator to assemble a battery;

[0027] or,

[0028] (III-2) Solution B is directly injected into the battery, and the battery is left to stand at 40 to 120° C. to obtain a solid-state battery.

[0029] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0030] The thermoelectric material composite electrolyte provided by the present invention has high ionic conductivity, voltage stability window and interface stability, can improve its rate performance under a wide temperature range, and when used in solid-state batteries, it exhibits good low-temperature rate performance and cycle stability.

[0031] The preparation method of the thermoelectric material composite electrolyte provided by the invention has simple operation, low cost and can be produced on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Performance comparison chart of Example 1 and Comparative Example 1 at low temperature -40°C. DETAILED DESCRIPTION

[0033] The following specific examples are intended to further illustrate the present invention rather than to limit the scope of protection of the claims.

[0034] The average particle size of the thermoelectric material used in the following specific examples is 150 nm.

[0035] Example 1

[0036] A polyamide polymer matrix is ​​selected, LiPF6 is selected as a lithium salt, tris(trimethylsilyl)phosphate TMSP is selected as an additive, and Li2SO4 is selected as a thermoelectric material, and the mass ratio is 1:5:1:2. First, N,N-methylenebisacrylamide monomer (at the same time, 1% AIBN by monomer mass), LiPF6, and TMSP are dissolved in an organic solvent ethyl methyl carbonate, so that the mass ratio of N,N-methylenebisacrylamide monomer: ethyl methyl carbonate is 1:9. After sufficient dissolution, the thermoelectric material Li2SO4 is added to the mixed solution, and after obtaining the mixed solution, it is injected into the battery, and then left to stand at 65°C for 10 hours to obtain a solid-state battery with an organic-inorganic electrolyte.

[0037] The battery uses high-nickel ternary NCM811 as the positive electrode, and the mass ratio of NCM811: carbon black: PVDF is 8:1:1. They are mixed evenly to form a slurry, which is evenly coated on aluminum foil and cut into positive electrode sheets with a diameter of 12 mm. Lithium metal is used as the negative electrode and assembled into a CR2016 button battery in a glove box.

[0038] Comparative Example 1

[0039] The only difference compared to Example 1 is that Li2SO4 is not added.

[0040] The solid-state batteries assembled in Example 1 and Comparative Example 1 were subjected to charge and discharge cycle tests under the same test equipment and test conditions, wherein the voltage range of the full battery test was 3 to 4.3 V and the test temperature was -40°C. Figure 1 The battery capacity of Example 1 is 105.32 mAh g at a current density of 1C. -1 After 100 cycles, the capacity is still 104.42 mAh g -1 , while the capacity of comparative example 1 at a current density of 1C is only 41.04 mAh g -1 After 100 cycles, the capacity is 40.18 mAh g -1 .

[0041] Example 2

[0042] Compared with Example 1, the only difference is that the thermoelectric material used is CaS, and its mass ratio remains unchanged. Its capacity is 94.21 mAh g at a current density of 1C. -1 After 100 cycles, the capacity is still 93.32 mAh g -1 .

[0043] Example 3

[0044] Compared with Example 1, the only difference is that the thermoelectric material used is CaSe, and its mass ratio remains unchanged. Its capacity is 92.78 mAh g at a current density of 1C. -1 After 100 cycles, the capacity is still 91.93 mAh g -1 .

[0045] Example 4

[0046] Compared with Example 1, the only difference is that the polymer matrix is ​​polyvinylidene fluoride, and the mass ratio remains unchanged. Its capacity is 98.58 mAh g at a current density of 1C. -1 After 100 cycles, the capacity is still 97.86 mAh g -1 .

[0047] Example 5

[0048] Compared with Example 1, the only difference is that the lithium salt is LiTFSI. Its capacity is 100.32 mAh g at a current density of 1C. -1 After 100 cycles, the capacity is still 99.45 mAh g -1 .

[0049] Example 6

[0050] Compared with Example 1, the only difference is that the ratio of polymer matrix to thermoelectric material is 1:4. Its capacity is 92.51 mAh g at a current density of 1C. -1 After 100 cycles, the capacity is still 90.13 mAh g -1 .

[0051] Example 7

[0052] Compared with Example 1, the only difference is that the ratio of polymer matrix to thermoelectric material is 1:0.2. Its capacity is 81.14 mAh g at a current density of 1C. -1 After 100 cycles, the capacity is still 80.03 mAh g -1 .

Claims

1. A thermoelectric material composite electrolyte, characterized in that: It includes a polymer matrix, lithium salt and thermoelectric material filler; the thermoelectric material filler includes at least one of Li2SO4 pyroelectric crystals, CaS pyroelectric crystals and CaSe pyroelectric crystals.

2. A thermoelectric material composite electrolyte according to claim 1, characterized in that: The particle size of the thermoelectric material filler is 1 nm to 1 μm.

3. A thermoelectric material composite electrolyte according to claim 1 or 2, characterized in that: It includes the following components by weight: 1 part of polymer matrix; 0.05-5 parts of lithium salt; Thermoelectric material 0.01 to 5 parts.

4. A thermoelectric material composite electrolyte according to claim 3, characterized in that: The polymer matrix includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride-trifluoroethylene), poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-hexafluoropropylene-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylic acid, polyacrylonitrile, epoxy resin, polyolefin nitrile, polyimide, and polyamide.

5. A thermoelectric material composite electrolyte according to claim 3, characterized in that: The lithium salt includes at least one of LiPF6, LiTFSI, and LiFSI.

6. A thermoelectric material composite electrolyte according to claim 3, characterized in that: Including no more than 5 parts by mass of additives; The additive includes at least one of phosphate ester, borate ester, silane coupling agent and sulfonate ester.

7. The method for preparing a thermoelectric material composite electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: (I) dissolving raw materials including polymer monomers and lithium salt in a solvent to form a solution A; (II) adding the thermoelectric material to solution A and stirring evenly to form solution B; (III) coating solution B onto a flat plate material and solidifying it into a thin film; or, injecting solution B into a battery and solidifying it into a shape.

8. The method for preparing a thermoelectric material composite electrolyte according to claim 7, characterized in that: The solvent comprises at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, tetrahydrofuran, N-methylpyrrolidone, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, ethylene glycol dimethyl ether, and ethylene glycol ethyl ether; The amount of the solvent used is 10 to 90 times the mass of the polymer.

9. A solid-state battery, characterized in that: The invention comprises the thermoelectric material composite electrolyte as claimed in any one of claims 1 to 6.

Citation Information

Cited By

  • Solid electrolyte membrane and preparation method and application thereof

    CN120497436A